Improved: The Impact of Education Management Information Systems (EMIS) on Data Management Efficiency in Islamic Senior High Schools - rosma rosma; Triwid Syafarotun Najah; Muhammad Redha Ansari (Al-Qalam Institue, 2026)
This study aims to analyze the impact of the implementation of the Education Management Information System (EMIS) on the efficiency of educational data management. Using a quantitative approach with an associative design, the research involved 66 respondents selected through purposive sampling. Data were collected through two questionnaires: one for assessing EMIS implementation (21 items) and one for evaluating educational data management efficiency (20 items). Both instruments were validated and tested for reliability using SPSS version 27. Data analysis included normality testing (Kolmogorov– Smirnov test), homogeneity testing (Levene’s test), and hypothesis testing (simple linear regression analysis). The results showed a significant effect of EMIS implementation on data management efficiency, with a significance value of <0.000 and an R Square value of 0.437. This indicates that EMIS contributes 43.7% to improving educational data management efficiency. The findings suggest that the adoption of EMIS can enhance administrative efficiency and facilitate more effective management of educational data.